2019
DOI: 10.1186/s13046-019-1299-4
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L-mediated resistance of paclitaxel and cisplatin is mediated by distinct regulatory mechanisms

Abstract: Background Cathepsin L (CTSL) is a cysteine protease known to have important roles in regulating cancer cellular resistance to chemotherapy. However mechanism underlying which regulates CTSL-mediated drug resistance remain largely unknown. Methods We used NSCLC cell lines: A549, A549/TAX (paclitaxel-resistant), A549/DDP (cisplatin-resistant), H460 and PC9 cells, to evaluate CTSL and drug resistance changes. Tumor specimens from 53 patients with NSCLC and Xenograft model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Moreover, previous research demonstrated that miR-149-5p increased the chemosensitivity of cisplatin on oral squamous cell carcinoma via inhibiting TGF-b2, p-Smad2, and p-Smad3 (Luo et al, 2019). Silencing TGF-b or smad3 in A549/TAX (paclitaxel resistant) cells decreased the expression of cathepsin L and enhanced their sensitivity to paclitaxel (Zhao et al, 2019). In addition, an expression vector carrying mutated or wild-type Smad3 was constructed and transfected into osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous research demonstrated that miR-149-5p increased the chemosensitivity of cisplatin on oral squamous cell carcinoma via inhibiting TGF-b2, p-Smad2, and p-Smad3 (Luo et al, 2019). Silencing TGF-b or smad3 in A549/TAX (paclitaxel resistant) cells decreased the expression of cathepsin L and enhanced their sensitivity to paclitaxel (Zhao et al, 2019). In addition, an expression vector carrying mutated or wild-type Smad3 was constructed and transfected into osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BbCI, which is also present in the seeds of B. bauhinioides and exhibits 84% primary structure similarity with BbKI [36], demonstrates a distinguished inhibitory specificity by inhibiting cysteine protease cathepsin L and serine proteases elastase and cathepsin G [17]. Although increasing cathepsin L-like activity may be correlated with malignant tumors [37,38] and elastase [28], rBbKl did not affect L929 cell viability, proliferation, or cell adhesion. Thus, the inhibitory specificity of rBbKI may have impacted its toxicity towards fibrosarcoma cells.…”
Section: Discussionmentioning
confidence: 96%
“…However, the function of CTSL in the complex process of tumorigenesis is not yet fully understood ( 23 ). It has been recently observed that CTSL is closely correlated with drug resistance in NSCLC ( 24 ). Our analyses showed that the upregulation of CTSL mRNA levels in LADC patients was associated with a higher risk of relapse and worse OS.…”
Section: Discussionmentioning
confidence: 99%